2015
DOI: 10.1037/lhb0000143
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the sex offender civil commitment trial outcomes in New York State.

Abstract: The present study analyzed sex offender civil management (i.e., civil commitment) legal proceedings in New York State and identified factors that predict trial results. Specifically, the current study compared a sample of 38 sex offenders who were released to the community after winning their civil management trials to 183 sex offenders who lost their civil management trials. Additionally, for the 183 sex offenders who lost their civil management trials, the current study compared 146 offenders who were ordere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 26 publications
2
18
2
3
Order By: Relevance
“…Indeed, an in-house coded construct of "deviant sexual preference" was the most robust predictor of an individual losing their civil management trial and being confined to inpatient treatment. Lu et al (2015) also found that minority race members were more likely to win civil management trials.…”
Section: Decision Making In Svp Proceedingsmentioning
confidence: 90%
“…Indeed, an in-house coded construct of "deviant sexual preference" was the most robust predictor of an individual losing their civil management trial and being confined to inpatient treatment. Lu et al (2015) also found that minority race members were more likely to win civil management trials.…”
Section: Decision Making In Svp Proceedingsmentioning
confidence: 90%
“…In Texas, incarcerated individuals who reached the point of having an SVP trial had significantly higher risk assessment scores than those not referred for SVP legal proceedings (Boccaccini et al, 2009). Findings from New York State, meanwhile, suggested once reviewed at a commitment hearing, actuarial risk scores did not differ for those ultimately committed or not committed (Lu et al, 2015).…”
Section: Trends In Svp Commitment Selectionmentioning
confidence: 92%
“…Levenson (2004) also found that SVPs were much more likely to have used a weapon during their index sex offense. A later study in New York found that factors suggestive of sexual deviance particularly predicted SVP commitment, including assessment of deviant sexual preferences or Pedophilia/Pedophilic Disorder, (Lu et al, 2015). Such assessments, however, have noted reliability limitations (see Perillo et al, 2014).…”
Section: Trends In Svp Commitment Selectionmentioning
confidence: 99%
“…Com relação aos AVSs psicóticos ou com retardo mental, são indivíduos com maior dificuldade para discernir quais são os comportamentos mais adequados para várias situações interpessoais ou sociais, bem como de entender quais são as consequências de seus ato com relação ao seu comportamento sexual. Não são capazes de perceber o caráter delituoso dos atos sexuais que praticam e, no geral, não manifestam um comportamento agressivo para com a vítima (Lu et al, 2015;Serafim et al, 2009). Os AVS situacionais tendem a ser os mais oportunistas e impulsivos, avaliam as características gerais da vítima e usam como critérios de escolha a disponibilidade da vítima e a oportunidade apresentada.…”
Section: Psicopatia E Autores De Violência Sexual Contra Crianças E Adolescentesunclassified